A Preliminary Study on the Design of C-Section Props - Dowy Pratama Sita; Muhammad Khafidh (Center for Biomechanics, Biomaterials, Biomechantronics and Biosignal Processing (CBOIM3S), 2021)
A cesarean section (c-section) is a surgical procedure aimed to deliver a baby by opening the abdominal wall and uterus. Now, c-section is one of the choices that are often chosen by mothers when giving birth. The knowledge and skills of c-section are important in education that focuses on obstetrics and obstetrics, especially for prospective specialist doctors taking the title of Specialist in Obstetrics and Gynecology (SpOG). Residents are required to be able to understand the procedure of c-section both in theory and practice. To train and improve c-section skills, one of the methods used is to use c-section props. This study aims to design and manufacture c-section props that resemble actual conditions and can be used repeatedly. The cesarean section props consist of three main parts, namely the abdominal body, the uterus, and the synthetic skin layer of the abdomen. The product master uses 3D printer results with PLA filament material. The props are made of RTV-48 silicone rubber and Polyurethane Foam with a mold made of fiberglass composite using the Hand Lay-UP method. The c-section props produced can provide an overview of the general cesarean surgery procedure.